HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN DIET PADA PASIEN GAGAL GINJAL KRONIK YANG DILAKUKAN HEMODIALISIS REGULER DI RUMAH SAKIT DARMO SURABAYA - Sri Sumilati (Universitas Nahdlatul Ulama Surabaya, 2018)
One of the therapies for the patients with chronic kidney failure is diet. In fact, the sufferers sometimes give less participation on the diet. One of the factors is the patient's knowledge about diet. Therefore, the purpose of this study was to find out the correlation between the knowledge level and the diet obedience level in the patients with chronic kidney failure having regular hemodialysis in Darmo Hospital. The design of study was analytic-observational. The population involved all of the patient with chronic kidney failure having regular hemodialysis in Darmo hospital. totally 63 people, in which 54 respondents were taken as the samples by using simple random sampling technique. The data were collected by using a questionnaire. The independent variable was the knowledge, whereas the dependent one was the diet obedience. Moreover, the data analysis was done by using Mann-Whitney's test with the significance level α = 0.05. The result of study showed that most of the respondents (59%) had high level of knowledge, whereas nearly all of them (83.3%) were obedient with their diet. Furthermore, the result of analysis showed that p = 0.220 so that p > α which meant that there was no significance correlation between knowledge and diet obedience. The conclusion of study was that the knowledge was not the main factor of the diet obedience. There are other supporting factors, such as experiences in having hemodialysis therapy that can affect someone to go on a diet. Hence, the nurses and their family should play a role more actively in giving counseling about the diet for chronic kidney failure.